Ethnomathematics: Utilization of Crock, Ladle, and Chopping Board for Learning Material of Geometry at the Elementary School - Ahmad Faqih; Odi Nurdiawan; Andi Setiawan (IndoMath: Indonesia Mathematics Education, 2021)
Mathematics and culture are not mutually exclusive. They work well together. It is because the help of ethnomathematics. Ethnomathematics is a learning approach of mathematics seeking a cultural approach in mathematical concepts. Â This study aims at exploring the shape of the crock (earthenware jar), ladle, and chopping board associated with learning materials of the two-dimensional and three-dimensional figure at the elementary school level. The research method used was descriptive qualitative, conducted adopting an ethnographic approach. The ethnographic approach consists of three stages: selection, writing and exploration. The study results found that the shape of the crock (earthenware jar), ladle, and chopping board contained mathematical elements, which are two-dimensional figure including circles and rectangles as well as three-dimensional figure including cuboid, cone and ball.